OPTIMALISASI DESAIN KEMASAN PRODUK UMKM DESA TENOGO KECAMATAN PANINGGARAN - Muhammad Taufiq Abadi (Community : Jurnal Pengabdian Pada Masyarakat, 2021)
The problems faced by the service partners of the Tenogo village UMKM actors include: the products produced are relatively only sold in the local market close to where they live, participants want village superior products such as coffee, chips, and other local preparations to be sold outside their area, so it is necessary to provide assistance, especially in hygienic product processing techniques, and attractive product packaging so that local products can be of interest to national consumers.The implementation of this service activity was carried out in Tenogo village, Paninggaran sub-district, Pekalongan district, which included training activities provided directly and consistent assistance. This activity was carried out within 3 days and was attended by 20 participants from business actors, youth and PKK mothers in Tenogo village and guided by 3 presenters. The implementation of this activity used several learning methods, including; lectures, practical methods and question and answer discussions.After carrying out community service activities in the form of lectures and training on the importance of product packaging and labeling for participants of business actors, teenagers and PKK mothers in Tenogo village, it can be concluded that: the use of product packaging is very important, starting from the introduction of types of packaging and its problems, the functions and uses of product packaging, packaging as a medium of information and promotion, types of packaging materials that are safe for health, attractive packaging design, and finally labeling and branding packaging is one of the strategies to improve the quality of local UMKM products for Tenogo residents.